PENYULUHAN KESEHATAN DALAM UPAYA PENCEGAHAN PENYAKIT DIARE PADA TEMPAT JAJANAN MAKANAN DI GORONTALO - Erfan AR. Lainjong; Agusrianto Yusuf (LPPM Universitas Bina Mandiri Gorontalo, 2022)
Street food is widespread in the community, especially for street vendors. One type of food disorder is diarrhea. Diarrhea disorders remain a public health problem in developing countries, including Indonesia, because they always appear in the form of Extraordinary Events (KLB) and coincide with large deaths. This study aims to provide knowledge to the public about the dangers of food that have been contaminated with bacteria and diseases caused by bacteria that pollute food and beverages. The method used is the descriptive method. The knowledge test uses a questionnaire through pre-test and post-test. This activity was carried out for 1 week, starting from November 20 - 27, 2021, at Bulota Village, Gorontalo Regency. The results showed that from 30 samples, before being given counselling (pre-test) showed that 73.33% of the public did not know about the characteristics and dangers of bacterial contamination in food and beverages. Public knowledge increased from 26.66% to 85.71% who knew about the characteristics and dangers of bacterial contamination in food and snacks after being given counselling (post-test).